The Non-Split Complement Line Domination in Graphs (Journal of Informatics and Mathematical Sciences, 2017)
Harary and Norman introduced the Line graph \(L(G)\). We introduced the split complement line domonation number by posting the disconnected property on the dominating sets of \(\overline{L(G)}\). In this paper, we study the connectedness property of dominating sets of \(\overline{L(G)}\) by defining non-split domination parameter. Also, we studied its graph theoretical properties in terms of elements of \(G\).
Keywords: Graph; Line graph; Domination number; Line domination number; Split line domination number; Split complement line domination number